2022
DOI: 10.3390/ijms23041967
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Promotes the Expansion of Cancer Stem Cells via TRPC3 Channels in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a highly aggressive cancer for which targeted therapeutic agents are limited. Growing evidence suggests that TNBC originates from breast cancer stem cells (BCSCs), and elucidation of the molecular mechanisms controlling BCSC proliferation will be crucial for new drug development. We have previously reported that the lysosphingolipid sphingosine-1-phosphate mediates the CSC phenotype, which can be identified as the ALDH-positive cell population in several types of human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Recent reports have provided additional support for IL-8 s role in TNBC progression. These studies implicate IL-8 in the development of bone, brain, and lung metastasis [33][34][35], epithelial mesenchymal transition [36], and expansion of cancer stem cells [37]. Our current findings indicate that only the EDA domain of fibronectin activated NFκB signaling and cytokine release in MDA-MB-468 cells, while both the EDA and III-1c domains elicited the response in MDA-MB-231 cells.…”
Section: Introductionsupporting
confidence: 51%
“…Recent reports have provided additional support for IL-8 s role in TNBC progression. These studies implicate IL-8 in the development of bone, brain, and lung metastasis [33][34][35], epithelial mesenchymal transition [36], and expansion of cancer stem cells [37]. Our current findings indicate that only the EDA domain of fibronectin activated NFκB signaling and cytokine release in MDA-MB-468 cells, while both the EDA and III-1c domains elicited the response in MDA-MB-231 cells.…”
Section: Introductionsupporting
confidence: 51%
“…The ALDEFLUOR kit (Stem Cell Technologies, Vancouver, BC, Canada) was used to detect CSC populations with high ALDH enzyme activity as was previously reported [12] . The cells were plated at a density of 1 × 10 5 cells in 60 mm culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…The sphere-forming assay was performed as previously described [12] . Briefly, cells were plated on ultra-low attachment 24-well plates (Corning, Acton, MA, USA) at a density of 5000 cells/mL in serum-free DMEM supplemented with N 2 (Gibco), 20 ng/mL basic fibroblast growth factor (R&D Systems, Minneapolis, MN, USA), and each concentration of the CSE.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, inhibition of the TRPC1-STIM1 complex may be an attractive target for the treatment of breast cancer metastasis. Naoya et al found that LPA/LPAR3 signaling and subsequent TRPC3 activation leaded to an increase in the number of breast cancer stem cells (BCSCs) through calcium-dependent transcriptional activation of IL-8 by NFAT ( Hirata et al, 2022 ). Polyunsaturated fatty acids (PUFA) and TRPC3 antagonists continuously inhibit the proliferation and migration of breast cancer cells ( Zhang et al, 2012b ), but the mechanism is still unclear.…”
Section: Trp Channels In the Mammary Glandmentioning
confidence: 99%